From Digital Leadership to Strategic Technology Management: How Digital Transformation Shapes Technology Governance in Higher Education - Kuswanto; Wargo; Delvia Muharramah (Zabags International Journal of Education, 2026)
Digital transformation has fundamentally reshaped how educational institutions adopt, integrate, and strategically manage technology. However, the extent to which digital leadership contributes to strategic technology management and the mechanisms underlying this relationship remain insufficiently understood. This study examines the influence of digital leadership on strategic technology management and investigates the mediating role of digital transformation in educational institutions. A quantitative explanatory research design was employed, with data collected from educational leaders, managers, and academic staff involved in institutional technology management. The proposed relationships were examined using structural equation modeling to assess both direct and indirect effects among the constructs. The findings indicate that digital leadership plays an important role in strengthening institutional digital transformation and strategic technology management. Digital transformation also demonstrates a significant contribution to strategic technology management by translating leadership vision and digital strategic orientation into organizational processes, technology integration, resource allocation, and technology governance. Furthermore, the mediation analysis demonstrates that digital transformation provides an important mechanism linking digital leadership with strategic technology management. These findings extend the educational technology literature by conceptualizing digital leadership not merely as an individual leadership competency but as a strategic organizational capability that facilitates the transformation of technology into an institutional resource. The study contributes practical implications for educational institutions by emphasizing the need to align digital leadership, transformation strategies, and technology governance to achieve sustainable and strategically managed educational technology ecosystems